Descriptive analysis of posts delivered by WeChat official accounts targeting Portugal news during the COVID-19 outbreak - Cheng, C.; Espanha, R. (Advances in Design and Digital Communication II. Springer Series in Design and Innovation, 2021)
Background: In the context of the ongoing COVID-19 pandemic, there is a recognized need to investigate the roles of mobile social media in disseminating up-to-date information. Several attempts have been made to analyze the hot topics which have been circulated across social media platforms and public information needs during the wave of COVID-19. In addition, user engagement behaviors have been the focus of much investigation in the search to strengthen communication efforts as well. There has also been substantial research undertaken on the roles of WeChat in terms of fighting COVID-19 in China. However, no known research has focused on official accounts which deliver posts about Portuguese news to Chinese living in Portugal during the COVID-19 crisis. Methods: By employing content analysis after recruiting 895 posts published by four official accounts, the present study seeks to explore its topic categories, follower information demands and the engagement level. Conclusions: The findings show that the topical categories of local news, updated data and policies and vaccination dominate the total of COVID-19-related posts during the period of observation. These four official accounts address urgent concerns of Chinese residents in Portugal by providing the latest news and reliable information sources. This paper also represents further strategies toward driving follower engagement by increasing media richness, regular posting, interaction and media convergence.